Nano surfactant and preparation method thereof

By alkali-cleaning and aminosilane coupling agent modification of graphene oxide, and combining with paraffin and nano-SiO2, an amphiphilic nanosurfactant is formed, which solves the unstableness of the existing oil repellent under high temperature and high salt conditions. The problem has significantly improved the crude oil recovery rate and oil displacement effect, and avoided pollution.

CN119144314APending Publication Date: 2024-12-17HEFEI PANORAMIC CHEMICAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411110175.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing oil repellent is unstable under high temperature and high salt conditions, which can easily cause chemical pollution in the groundwater of the oil field, and the oil production effect is poor, making it difficult to improve the recovery rate of crude oil.

Method used

Using a nanosurfactant preparation method, the nano SiO2 with amphiphilicity is formed by alkali washing pretreatment and aminosilane coupling agent modification by combining paraffin and epoxy silane coupling agent modification. and stable composite structure, used to reduce the surface tension of the system and improve the oil displacement effect.

Benefits of technology

It significantly improves the oil repellent effect and crude oil recovery rate under high temperature and high salt, enhances the structural stability of nanosurfactants, and synergistically improves the oil repellent performance and avoids pollution problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004991954610000111
    Figure BDA0004991954610000111
Patent Text Reader

Abstract

The preparation method comprises the following steps: mixing and emulsifying an aminated graphene oxide aqueous dispersion and paraffin, cooling the prepared emulsion to obtain paraffin beads, sequentially reacting the paraffin beads with nano SiO2 modified by an epoxy silane coupling agent and dodecyl glycidyl ether in absolute ethyl alcohol to obtain the nano surfactant. And adding into trichloromethane to dissolve the paraffin, and collecting to obtain the nano surfactant. The nano surfactant disclosed by the invention can be used as an oil displacement agent in oil exploitation, can effectively improve the oil displacement effect under high temperature and high salt, and obviously improves the recovery rate of crude oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano surfactants, in particular to a nano surfactant and a preparation method thereof. Background Art

[0002] Oil is one of the main energy sources in the world. With the growing demand for energy, oil mining and production technology is particularly important for the development of the national economy. In order to improve the recovery rate of oil fields, the commonly used method is to use oil displacement agents in the oil recovery process. At present, commonly used oil displacement agents include polymers, surfactants and nanomaterials. Polymer and surfactant oil displacement agents are often sensitive to high temperature and high salt conditions, and these oil displacement agents also have problems such as large usage and easy chemical pollution of oil field groundwater. Nanomaterials have the characteristics of small size and large specific surface area. They can change the wettability of rocks, reduce the oil-water interfacial tension, and reduce the adsorption of crude oil on the surface and internal micropores of rocks, so that crude oil is easy to peel off and be displaced during the oil field injection process, thereby greatly improving the recovery rate of oil fields. Among them, nano surfactants with excellent amphiphilicity can significantly enhance the stability of emulsions, thereby better improving the oil recovery effect. Therefore, developing new nano surfactants to further improve crude oil recovery has become an important research direction of oil recovery technology. Summary of the invention

[0003] Based on the technical problems existing in the background technology, the present invention proposes a nano surfactant and a preparation method thereof.

[0004] The present invention provides a method for preparing a nano surfactant, comprising the following steps:

[0005] S1. Add sodium hydroxide to the graphene oxide aqueous dispersion, heat at 70-90° C. for 3-5 h, then cool and centrifuge, wash the collected solid matter with deionized water until neutral, and dry to obtain an intermediate product A; add the intermediate product A to a hydrochloric acid aqueous solution with a concentration of 0.1-0.2 mol / L, heat at 70-90° C. for 1-2 h, then cool and centrifuge, wash the collected solid matter with deionized water until neutral, and dry to obtain pretreated graphene oxide;

[0006] S2, adding the pretreated graphene oxide to the aminosilane coupling agent hydrolyzate and ultrasonically dispersing it uniformly, then heating it at 70-80° C. for reaction for 3-5 hours, centrifuging it after cooling, and drying it to obtain an amino-modified graphene oxide material;

[0007] S3, adding the amino graphene oxide material into deionized water and uniformly dispersing it by ultrasonic to obtain an amino graphene oxide aqueous dispersion, mixing the amino graphene oxide aqueous dispersion with liquid paraffin at 75-80°C, emulsifying it by high-speed shearing, and solidifying the obtained emulsion in an ice water bath after the emulsification, washing and drying to obtain paraffin beads; adding nano-SiO2 modified by epoxy silane coupling agent into anhydrous ethanol and uniformly dispersing it, then adding the paraffin beads, stirring and reacting at 40-45°C for 6-10h, then adding dodecyl glycidyl ether, continuing to stir and react at 40-45°C for 1-2h, filtering after the reaction, washing the collected solid matter with anhydrous ethanol, adding chloroform to dissolve the paraffin, and collecting the nano surfactant.

[0008] Preferably, in S1, the solid content of the graphene oxide aqueous dispersion is 0.05-0.2%, and the mass ratio of the graphene oxide aqueous dispersion to sodium hydroxide is 100:0.2-0.5.

[0009] Preferably, the particle size of the graphene oxide is 50 to 200 nm.

[0010] Preferably, in S1, the mass ratio of the intermediate product A to the aqueous hydrochloric acid solution is 1:100-200.

[0011] Preferably, in S2, the mass ratio of the pretreated graphene oxide to the aminosilane coupling agent hydrolyzate is 0.03-0.05:100, and the aminosilane coupling agent hydrolyzate is prepared from aminosilane coupling agent, anhydrous ethanol and deionized water in a mass ratio of 2-3:70-90:10-30.

[0012] In the present invention, the aminosilane coupling agent hydrolyzate is prepared by a conventional method, for example, the aminosilane coupling agent is added to anhydrous ethanol and deionized water, mixed evenly, and hydrolyzed for 10 to 15 minutes to obtain the hydrolyzate.

[0013] Preferably, the aminosilane coupling agent is at least one of silane coupling agents KH-550, KH-602, and KH-792.

[0014] Preferably, in S3, the mass ratio of the amino-modified graphene oxide material to deionized water and paraffin is 1:50-100:5-10.

[0015] Preferably, in S3, the mass ratio of the paraffin beads to the nano-SiO2 modified by epoxy silane coupling agent and dodecyl glycidyl ether is 10:0.2-0.5:1-2.

[0016] Preferably, in S3, the nano-SiO2 modified by the epoxy silane coupling agent is added to anhydrous ethanol with a mass equivalent to 200 to 500 times of the mass of the nano-SiO2 modified by the epoxy silane coupling agent and dispersed evenly.

[0017] Preferably, the preparation method of the epoxy silane coupling agent modified nano-SiO2 is: adding hydrophilic nano-SiO2 to the epoxy silane coupling agent hydrolyzate and ultrasonically dispersing it uniformly, then heating it at 70-80°C for reaction for 3-5h, cooling it, centrifuging it, and drying it to obtain the product.

[0018] Preferably, the mass ratio of the hydrophilic nano-SiO2 to the epoxy silane coupling agent hydrolyzate is 0.1-0.5:100, and the epoxy silane coupling agent hydrolyzate is prepared from epoxy silane coupling agent, anhydrous ethanol and deionized water in a mass ratio of 2-3:70-90:10-30.

[0019] In the present invention, the epoxy silane coupling agent hydrolyzate is prepared by a conventional method, for example, by adding the epoxy silane coupling agent to anhydrous ethanol and deionized water, mixing them evenly, and hydrolyzing them for 10 to 15 minutes to obtain the hydrolyzate.

[0020] Preferably, the particle size of the hydrophilic nano-SiO2 is 10 to 20 nm.

[0021] Preferably, the epoxy silane coupling agent is silane coupling agent KH-560.

[0022] Preferably, in S3, the rotation speed of the high-speed shear emulsification is 2000-3000 r / min, and the time is 1-2 h.

[0023] The invention also provides a nano surfactant, which is prepared by the preparation method.

[0024] The beneficial effects of the present invention are as follows:

[0025] In the present invention, graphene oxide is firstly subjected to alkali washing pretreatment to fully remove oxygen-containing groups on its surface, and then modified with an aminosilane coupling agent to obtain graphene oxide material containing amino groups on the surface; on this basis, paraffin beads coated with graphene oxide material containing amino groups are obtained by mixing and emulsifying with paraffin wax, and half-surface protection is formed for the amino groups of the part of graphene oxide not exposed on the surface of the paraffin beads; the paraffin beads are then mixed with anhydrous ethanol dispersion of nano-SiO2 modified by an epoxysilane coupling agent for reaction, and the amino groups of the part of graphene oxide exposed on the surface of the paraffin beads react with the epoxy groups of the nano-SiO2, so that the nano-SiO2 is loaded on the graphene oxide, and then the graphene oxide is continuously reacted with dodecyl glycidyl ether having a hydrophobic long chain, so that the exposed surface of the graphene oxide becomes a hydrophobic surface, and the paraffin is washed off with chloroform at this time, so that an amphiphilic nano-surfactant having amino hydrophilic groups on one side and coated with hydrophobic nano-SiO2 and a hydrophobic long chain on the other side is obtained. The nano surfactant of the present invention not only has the amphiphilic characteristics of surfactants, but also can play the effect of reducing the surface tension of the system and emulsifying and solubilizing, thereby improving the oil displacement effect under high temperature and high salt; and due to the composite structure of graphene oxide-nano SiO2, not only the structural stability of the nano surfactant is improved by the steric effect, thereby improving the stability of the nano surfactant under high temperature and high salt, thereby better exerting its oil displacement performance under high temperature and high salt environment, but also on the basis of the peeling effect of flaky graphene oxide on crude oil attached to rocks, combined with the high specific surface area and excellent interfacial activity of nano SiO2, thereby playing a synergistic role, realizing a great improvement in the oil displacement effect. The nano surfactant of the present invention can be used as an oil displacement agent in oil production, can effectively improve the oil displacement effect under high temperature and high salt, and significantly improve the recovery rate of crude oil. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is described in detail below through specific embodiments.

[0027] In the following examples and comparative examples, graphene oxide and hydrophilic nano-SiO2 are both commercially available products. Graphene oxide is prepared by the Hummers method and has a particle size of 50 to 200 nm; the particle size of hydrophilic nano-SiO2 is 10 to 20 nm.

[0028] Example 1

[0029] A method for preparing a nano surfactant comprises the following steps:

[0030] S1. Adding sodium hydroxide to a graphene oxide aqueous dispersion having a solid content of 0.1%, heating at 70° C. for 3 h, then cooling and centrifuging, washing the collected solid matter with deionized water until neutral, and drying to obtain an intermediate product A, wherein the mass ratio of the graphene oxide aqueous dispersion to the sodium hydroxide is 100:0.3;

[0031] The intermediate product A was added to a hydrochloric acid aqueous solution with a concentration of 0.1 mol / L, heated at 70° C. for 1 h, then cooled and centrifuged, and the collected solid matter was washed with deionized water until neutral, and dried to obtain pretreated graphene oxide, wherein the mass ratio of the intermediate product A to the hydrochloric acid aqueous solution was 1:100;

[0032] S2, adding the pretreated graphene oxide to the silane coupling agent KH-550 hydrolyzate to disperse it evenly by ultrasonication, then heating it at 70°C for reaction for 3h, centrifuging it after cooling, and drying it to obtain an amino graphene oxide material, wherein the mass ratio of the pretreated graphene oxide to the silane coupling agent KH-550 hydrolyzate is 0.04:100, and the silane coupling agent KH-550 hydrolyzate is prepared from the silane coupling agent KH-550, anhydrous ethanol, and deionized water in a mass ratio of 2:75:25;

[0033] S3, adding the aminated graphene oxide material to deionized water and uniformly dispersing it by ultrasonication to obtain an aminated graphene oxide aqueous dispersion, uniformly mixing the aminated graphene oxide aqueous dispersion with liquid paraffin at 75°C, and emulsifying it at a high speed of 2500r / min for 1h. After the emulsification, the obtained emulsion is placed in an ice water bath for solidification, washed with anhydrous ethanol, and dried to obtain paraffin beads, wherein the mass ratio of the aminated graphene oxide material to deionized water and paraffin is 1:80:9;

[0034] The nano-SiO2 modified by epoxy silane coupling agent is added to anhydrous ethanol equivalent to 500 times the mass of the nano-SiO2 modified by epoxy silane coupling agent and dispersed evenly, and then paraffin beads are added, stirred and reacted at 40°C for 10 hours, and then dodecyl glycidyl ether is added, and the stirring reaction is continued at 40°C for 2 hours. After the reaction is completed, it is filtered, and the collected solid matter is washed with anhydrous ethanol, and then added to chloroform to dissolve the paraffin. After centrifugation, the collected solid matter is washed with anhydrous ethanol, and dried to obtain a nano surfactant, wherein the paraffin beads The mass ratio of nano-SiO2 modified with epoxy silane coupling agent and dodecyl glycidyl ether is 10:0.2:1; the preparation method of nano-SiO2 modified with epoxy silane coupling agent is as follows: hydrophilic nano-SiO2 is added to silane coupling agent KH-560 hydrolyzate at a mass ratio of 0.1:100 and ultrasonically dispersed evenly, then heated at 70°C for reaction for 3h, centrifuged after cooling, and dried to obtain the hydrolyzate of silane coupling agent KH-560. The hydrolyzate of silane coupling agent KH-560 is prepared by silane coupling agent KH-560, anhydrous ethanol, and deionized water at a mass ratio of 2:75:25.

[0035] Example 2

[0036] A method for preparing a nano surfactant comprises the following steps:

[0037] S1. Adding sodium hydroxide to a graphene oxide aqueous dispersion having a solid content of 0.05%, heating at 80° C. for 4 h, cooling, centrifuging, washing the collected solid matter with deionized water until neutral, and drying to obtain an intermediate product A, wherein the mass ratio of the graphene oxide aqueous dispersion to the sodium hydroxide is 100:0.2;

[0038] The intermediate product A was added to a 0.15 mol / L hydrochloric acid aqueous solution, heated at 80° C. for 1.5 h, then cooled and centrifuged, and the collected solid matter was washed with deionized water until neutral, and dried to obtain pretreated graphene oxide, wherein the mass ratio of the intermediate product A to the hydrochloric acid aqueous solution was 1:150;

[0039] S2, adding the pretreated graphene oxide to the silane coupling agent KH-550 hydrolyzate to disperse it evenly by ultrasonication, then heating it at 75°C for reaction for 4 hours, centrifuging it after cooling, and drying it to obtain an amino graphene oxide material, wherein the mass ratio of the pretreated graphene oxide to the silane coupling agent KH-550 hydrolyzate is 0.03:100, and the silane coupling agent KH-550 hydrolyzate is prepared from the silane coupling agent KH-550, anhydrous ethanol, and deionized water in a mass ratio of 2.5:80:20;

[0040] S3, adding the aminated graphene oxide material to deionized water and uniformly dispersing it by ultrasonication to obtain an aminated graphene oxide aqueous dispersion, uniformly mixing the aminated graphene oxide aqueous dispersion with liquid paraffin at 78°C, and emulsifying it at a high speed of 2000r / min for 1.5h, and after the emulsification, placing the obtained emulsion in an ice water bath for solidification, washing with anhydrous ethanol, and drying to obtain paraffin beads, wherein the mass ratio of the aminated graphene oxide material to deionized water and paraffin is 1:50:5;

[0041] The nano-SiO2 modified by epoxy silane coupling agent is added to anhydrous ethanol equivalent to 400 times the mass of the nano-SiO2 modified by epoxy silane coupling agent and dispersed evenly, and then paraffin beads are added, stirred and reacted at 42°C for 8 hours, and then dodecyl glycidyl ether is added, and the stirring reaction is continued at 42°C for 1.5 hours. After the reaction is completed, it is filtered, and the collected solid matter is washed with anhydrous ethanol, and then added to chloroform to dissolve the paraffin. After centrifugation, the collected solid matter is washed with anhydrous ethanol and dried to obtain a nano surfactant, in which the paraffin beads and The mass ratio of nano-SiO2 modified by epoxy silane coupling agent and dodecyl glycidyl ether is 10:0.3:1.5; the preparation method of nano-SiO2 modified by epoxy silane coupling agent is as follows: hydrophilic nano-SiO2 is added to the hydrolyzate of silane coupling agent KH-560 at a mass ratio of 0.1:100 and ultrasonically dispersed evenly, then heated at 75°C for reaction for 4 hours, centrifuged after cooling, and dried to obtain the hydrolyzate of silane coupling agent KH-560. The hydrolyzate of silane coupling agent KH-560 is prepared by silane coupling agent KH-560, anhydrous ethanol, and deionized water at a mass ratio of 2.5:80:20.

[0042] Example 3

[0043] A method for preparing a nano surfactant comprises the following steps:

[0044] S1. Adding sodium hydroxide to a graphene oxide aqueous dispersion having a solid content of 0.2%, heating at 90° C. for 5 h, cooling, centrifuging, washing the collected solid matter with deionized water until neutral, and drying to obtain an intermediate product A, wherein the mass ratio of the graphene oxide aqueous dispersion to the sodium hydroxide is 100:0.2-0.5;

[0045] The intermediate product A was added to a hydrochloric acid aqueous solution with a concentration of 0.2 mol / L, heated at 90° C. for 2 h, then cooled and centrifuged, and the collected solid matter was washed with deionized water until neutral, and dried to obtain pretreated graphene oxide, wherein the mass ratio of the intermediate product A to the hydrochloric acid aqueous solution was 1:200;

[0046] S2, adding the pretreated graphene oxide to the silane coupling agent KH-550 hydrolyzate to disperse it evenly by ultrasonication, then heating it at 80°C for reaction for 5h, centrifuging it after cooling, and drying it to obtain an amino graphene oxide material, wherein the mass ratio of the pretreated graphene oxide to the silane coupling agent KH-550 hydrolyzate is 0.05:100, and the silane coupling agent KH-550 hydrolyzate is prepared from the silane coupling agent KH-550, anhydrous ethanol, and deionized water in a mass ratio of 3:70:30;

[0047] S3, adding the aminated graphene oxide material to deionized water and uniformly dispersing it by ultrasonication to obtain an aminated graphene oxide aqueous dispersion, uniformly mixing the aminated graphene oxide aqueous dispersion with liquid paraffin at 80°C, and emulsifying it at a high speed of 3000r / min for 2h, and after the emulsification, placing the obtained emulsion in an ice water bath for solidification, washing with anhydrous ethanol, and drying to obtain paraffin beads, wherein the mass ratio of the aminated graphene oxide material to deionized water and paraffin is 1:100:10;

[0048] The nano-SiO2 modified by epoxy silane coupling agent is added to anhydrous ethanol equivalent to 200 times the mass of the nano-SiO2 modified by epoxy silane coupling agent and dispersed evenly, and then paraffin beads are added, stirred and reacted at 45°C for 6 hours, and then dodecyl glycidyl ether is added, and the stirring reaction is continued at 45°C for 1 hour. After the reaction is completed, it is filtered, and the collected solid matter is washed with anhydrous ethanol, and then added to chloroform to dissolve the paraffin. After centrifugation, the collected solid matter is washed with anhydrous ethanol, and the nano-surfactant is obtained after drying, wherein the paraffin beads The mass ratio of nano-SiO2 modified with epoxy silane coupling agent and dodecyl glycidyl ether is 10:0.5:2; the preparation method of nano-SiO2 modified with epoxy silane coupling agent is as follows: hydrophilic nano-SiO2 is added to the hydrolyzate of silane coupling agent KH-560 at a mass ratio of 0.1:100 and ultrasonically dispersed evenly, then heated at 80°C for reaction for 5 hours, centrifuged after cooling, and dried to obtain the hydrolyzate of silane coupling agent KH-560. The hydrolyzate of silane coupling agent KH-560 is prepared by silane coupling agent KH-560, anhydrous ethanol, and deionized water at a mass ratio of 3:70:30.

[0049] Comparative Example 1

[0050] Preparation of graphene oxide-nano-SiO2 mixed surfactant:

[0051] (1) Preparation of amphiphilic graphene oxide:

[0052] Adding sodium hydroxide to a graphene oxide aqueous dispersion having a solid content of 0.1%, heating at 70° C. for 3 h, then cooling and centrifuging, washing the collected solid matter with deionized water until neutral, and drying to obtain an intermediate product A, wherein the mass ratio of the graphene oxide aqueous dispersion to the sodium hydroxide is 100:0.3;

[0053] The intermediate product A was added to a hydrochloric acid aqueous solution with a concentration of 0.1 mol / L, heated at 70° C. for 1 h, then cooled and centrifuged, and the collected solid matter was washed with deionized water until neutral, and dried to obtain pretreated graphene oxide, wherein the mass ratio of the intermediate product A to the hydrochloric acid aqueous solution was 1:100;

[0054] The pretreated graphene oxide was added to the hydrolyzate of silane coupling agent KH-550 and ultrasonically dispersed uniformly, and then heated at 70°C for reaction for 3 hours, centrifuged after cooling, and dried to obtain an amino graphene oxide material, wherein the mass ratio of the pretreated graphene oxide to the hydrolyzate of silane coupling agent KH-550 was 0.04:100, and the hydrolyzate of silane coupling agent KH-550 was prepared by silane coupling agent KH-550, anhydrous ethanol, and deionized water in a mass ratio of 2:75:25;

[0055] The aminated graphene oxide material is added into deionized water and ultrasonically dispersed uniformly to obtain an aminated graphene oxide aqueous dispersion, the aminated graphene oxide aqueous dispersion is uniformly mixed with liquid paraffin at 75°C, and high-speed shear emulsification is performed at a speed of 2500r / min for 1h. After the emulsification, the obtained emulsion is placed in an ice water bath for solidification, washed with anhydrous ethanol, and dried to obtain paraffin beads, wherein the mass ratio of the aminated graphene oxide material to deionized water and paraffin is 1:80:9;

[0056] The paraffin beads were evenly dispersed in anhydrous ethanol equivalent to 10 times the mass of the paraffin beads, and then dodecyl glycidyl ether was added and stirred for reaction at 40°C for 2 hours. After the reaction was completed, the collected solid matter was filtered, washed with anhydrous ethanol, and added to chloroform to dissolve the paraffin. After centrifugation, the collected solid matter was washed with anhydrous ethanol and dried to obtain amphiphilic graphene oxide.

[0057] (2) Preparation of amphiphilic nano-SiO2:

[0058] The hydrophilic nano-SiO2 was added to the hydrolyzate of silane coupling agent KH-550 and dispersed uniformly by ultrasonication, and then heated at 70°C for reaction for 3 hours, centrifuged after cooling, and dried to obtain amino nano-SiO2, wherein the mass ratio of the hydrophilic nano-SiO2 to the hydrolyzate of silane coupling agent KH-550 was 0.04:100, and the hydrolyzate of silane coupling agent KH-550 was prepared by silane coupling agent KH-550, anhydrous ethanol, and deionized water in a mass ratio of 2:75:25;

[0059] S3, adding aminated nano-SiO2 to deionized water and uniformly dispersing it by ultrasonication to obtain an aminated nano-SiO2 aqueous dispersion, uniformly mixing the aminated nano-SiO2 aqueous dispersion with liquid paraffin at 75°C, and emulsifying it at a high speed of 2500r / min for 1h. After the emulsification, solidifying the obtained emulsion in an ice water bath, washing with anhydrous ethanol, and drying, obtaining paraffin beads, wherein the mass ratio of aminated nano-SiO2 to deionized water and paraffin is 1:80:9;

[0060] The paraffin beads are evenly dispersed in anhydrous ethanol equivalent to 10 times the mass of the paraffin beads, and then dodecyl glycidyl ether is added and stirred for reaction at 40°C for 2 hours. After the reaction is completed, the collected solid matter is filtered, washed with anhydrous ethanol, and added to chloroform to dissolve the paraffin. After centrifugation, the collected solid matter is washed with anhydrous ethanol and dried to obtain amphiphilic nano-SiO2.

[0061] (3) The amphiphilic graphene oxide prepared above is mixed with amphiphilic nano-SiO2 at a mass ratio of 1:0.2 to obtain a graphene oxide-nano-SiO2 mixed surfactant.

[0062] Test example

[0063] The nano surfactant of Example 1 and the amphiphilic graphene oxide, amphiphilic nano-SiO2 and graphene oxide-nano-SiO2 mixed surfactant in Comparative Example 1 were respectively formulated into oil-displacing agents, and the oil displacement performance of each of the above oil-displacing agents was studied, and the test method was as follows:

[0064] Model making stage: prepare a one-dimensional sand-filled model (the inner diameter of the sand-filled model is 25 mm, the length is 500 mm, and the middle is filled with quartz sand), first inject 5000 mg / L NaCl solution into the one-dimensional sand-filled model, and then inject crude oil (viscosity is 45.1 mPa.s at 70°C).

[0065] Water flooding stage: 5000 mg / L NaCl brine was used to displace the crude oil until the water content reached 95%.

[0066] Oil-displacing agent displacement stage: The nano-surfactant of Example 1 and the amphiphilic graphene oxide, amphiphilic nano-SiO2 and graphene oxide-nano-SiO2 mixed surfactant in Comparative Example 1 were respectively prepared into a dispersion with a concentration of 0.2wt% using 5000mg / L NaCl solution as an oil-displacing agent, and the above-prepared oil-displacing agents were injected into the model at a dosage of 0.3PV for displacement, and then 5000mg / L NaCl solution was injected until the water content reached 95%.

[0067] The above test was carried out at 70°C.

[0068] The recovery rate (increased recovery rate = total recovery rate - water flooding stage recovery rate) of the nano surfactant of Example 1 and the amphiphilic graphene oxide, amphiphilic nano-SiO2 and graphene oxide-nano-SiO2 mixed surfactant in Comparative Example 1 as oil displacement agents is shown in Table 1:

[0069] Table 1

[0070]

[0071] As can be seen from Table 1, the nanosurfactant of Example 1 of the present invention as an oil-displacing agent can significantly improve the oil displacement effect and crude oil recovery rate compared with a single amphiphilic graphene oxide and amphiphilic nano-SiO2, and a graphene oxide-nano-SiO2 mixed surfactant obtained by simply blending and compounding amphiphilic graphene oxide and amphiphilic nano-SiO2. This is because in the present invention, the nano-surfactant not only has the amphiphilicity of half-surface containing hydrophilic amino groups and half-surface containing hydrophobic long chains, which can reduce the surface tension of the system and emulsify and solubilize, thereby improving the oil recovery effect under high temperature and high salinity, but also in the synthesis process, the nano-SiO2 modified by epoxy silane coupling agent is combined with the hydrophobic surface of the amphiphilic graphene oxide to form a composite structure of graphene oxide-nano-SiO2, which not only improves the structural stability of the nano-surfactant through the steric effect, thereby improving the stability of the nano-surfactant under high temperature and high salinity, thereby better exerting its oil recovery performance under high temperature and high salinity environment, but also can combine the high specific surface area and excellent interface activity of nano-SiO2 on the basis of the stripping effect of flaky graphene oxide on crude oil attached to rocks, thereby playing a synergistic role and greatly improving the oil recovery effect.

[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a nano surfactant, characterized in that: The following steps are involved: S1. Add sodium hydroxide to the graphene oxide aqueous dispersion, heat at 70-90° C. for 3-5 h, then cool and centrifuge, wash the collected solid matter with deionized water until neutral, and dry to obtain an intermediate product A; add the intermediate product A to a hydrochloric acid aqueous solution with a concentration of 0.1-0.2 mol / L, heat at 70-90° C. for 1-2 h, then cool and centrifuge, wash the collected solid matter with deionized water until neutral, and dry to obtain pretreated graphene oxide; S2, adding the pretreated graphene oxide to the aminosilane coupling agent hydrolyzate and ultrasonically dispersing it uniformly, then heating it at 70-80° C. for reaction for 3-5 hours, centrifuging it after cooling, and drying it to obtain an amino-modified graphene oxide material; S3, adding the amino graphene oxide material into deionized water and uniformly dispersing it by ultrasonic to obtain an amino graphene oxide aqueous dispersion, mixing the amino graphene oxide aqueous dispersion with liquid paraffin at 75-80°C, emulsifying it by high-speed shearing, and solidifying the obtained emulsion in an ice water bath after the emulsification, washing and drying to obtain paraffin beads; adding nano-SiO2 modified by epoxy silane coupling agent into anhydrous ethanol and uniformly dispersing it, then adding the paraffin beads, stirring and reacting at 40-45°C for 6-10h, then adding dodecyl glycidyl ether, continuing to stir and react at 40-45°C for 1-2h, filtering after the reaction, washing the collected solid matter with anhydrous ethanol, adding chloroform to dissolve the paraffin, and collecting the nano surfactant.

2. The method for preparing a nano surfactant according to claim 1, characterized in that: In S1, the solid content of the graphene oxide aqueous dispersion is 0.05-0.2%, and the mass ratio of the graphene oxide aqueous dispersion to sodium hydroxide is 100:0.2-0.

5.

3. The method for preparing a nano surfactant according to claim 1, characterized in that: The particle size of the graphene oxide is 50 to 200 nm.

4. The method for preparing a nano surfactant according to claim 1, characterized in that: In S2, the mass ratio of the pretreated graphene oxide to the aminosilane coupling agent hydrolyzate is 0.03-0.05:100, and the aminosilane coupling agent hydrolyzate is prepared from aminosilane coupling agent, anhydrous ethanol, and deionized water in a mass ratio of 2-3:70-90:10-30.

5. The method for preparing a nano surfactant according to claim 1, characterized in that: In S3, the mass ratio of the amino-modified graphene oxide material to deionized water and paraffin is 1:50-100:5-10.

6. The method for preparing a nano surfactant according to claim 1, characterized in that: In S3, the mass ratio of the paraffin beads to the nano-SiO2 modified by epoxy silane coupling agent and dodecyl glycidyl ether is 10:0.2-0.5:1-2.

7. The method for preparing a nano surfactant according to claim 1, characterized in that: The preparation method of the epoxy silane coupling agent modified nano-SiO2 is as follows: adding hydrophilic nano-SiO2 into the hydrolyzate of the epoxy silane coupling agent and uniformly dispersing it by ultrasonic, then heating it at 70-80°C for reaction for 3-5h, cooling it, centrifuging it, and drying it to obtain the product.

8. The method for preparing a nano surfactant according to claim 7, characterized in that: The mass ratio of the hydrophilic nano-SiO2 to the epoxy silane coupling agent hydrolyzate is 0.1-0.5:100, and the epoxy silane coupling agent hydrolyzate is prepared from the epoxy silane coupling agent, anhydrous ethanol and deionized water in a mass ratio of 2-3:70-90:10-30.

9. The method for preparing a nano surfactant according to claim 8, characterized in that: The particle size of the hydrophilic nano-SiO2 is 10-20 nm.

10. A nano surfactant, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Cited By

  • Graphene oxide temperature-resistant foam stabilizer capable of maintaining amphipathy under wide pH range and preparation method of graphene oxide temperature-resistant foam stabilizer

    CN119823743A